Analysis of administrative service quality in ensuring the accuracy of pension benefit payments at PTPN IV regional 1 - Ade Kurnia Sari; Annio Indah Lestari Nasution; Nurlaila Nurlaila (Trigin Publisher, 2025)
This study aims to analyze the quality of administrative services in ensuring the accuracy of pension benefit payments at PTPN IV Regional 1 by using a descriptive qualitative approach through interviews and observations. The background of this research stems from the importance of administrative service effectiveness in ensuring the welfare of retirees as part of sustainable human resource governance. The quality of administrative services is a strategic factor in building public trust and ensuring that retirees’ financial rights are fulfilled accurately and on time. The results show that, in general, administrative services have been carried out in accordance with standards, particularly in terms of payment timeliness, compliance with administrative procedures, and the reliability of digital systems. However, several challenges remain, such as limited digital literacy among elderly participants, technical issues in the application, and insufficient staffing, making the services less responsive. This condition indicates a gap between service standards and the capabilities of some participants, requiring optimization strategies such as personalized assistance, automatic reminder systems, manual service alternatives, and human resource capacity building to make services more inclusive, adaptive, and capable of ensuring accurate pension payments sustainably. Theoretically, this study contributes to the development of the concept of public service quality within the context of pension administration, particularly regarding the dimensions of responsiveness and equitable access for vulnerable groups. Practically, the findings are expected to serve as a foundation for PTPN IV management in formulating policies to enhance digital-based administrative services that are more inclusive and participant satisfaction-oriented.